2021
DOI: 10.1155/2021/5147069
|View full text |Cite
|
Sign up to set email alerts
|

Sesamin Protects against and Ameliorates Rat Intestinal Ischemia/Reperfusion Injury with Involvement of Activating Nrf2/HO‐1/NQO1 Signaling Pathway

Abstract: Intestinal ischemia-reperfusion (I/R) may induce cell/tissue injuries, leading to multiple organ failure. Based on our preexperiments, we proposed that sesamin could protect against and ameliorate intestinal I/R injuries and related disorders with involvement of activating Nrf2 signaling pathway. This proposal was evaluated using SD intestinal I/R injury rats in vivo and hypoxia/reoxygenation- (H/R-) injured rat small intestinal crypt epithelial cell line (IEC-6 cells) in vitro. Sesamin significantly alleviate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…Nrf2 controls the expression of a series of antioxidant genes and is the core factor in regulating antioxidant stress [ 14 ]. It has been proved that Nrf2 can enhance the antioxidant capacity of cells by upregulating the expression of detoxification enzyme genes such as NAD(P)H, quinone oxidoreductase (NQO1), and heme oxidase-1(HO-1) [ 15 , 16 ]. The protective effect of Nrf2 on the heart has also been confirmed in many animal models, including uncompensated cardiac remodeling and cardiac dysfunction caused by aortic arch constriction (TAC), ventricular remodeling, and cardiac dysfunction caused by myocardial infarction, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 controls the expression of a series of antioxidant genes and is the core factor in regulating antioxidant stress [ 14 ]. It has been proved that Nrf2 can enhance the antioxidant capacity of cells by upregulating the expression of detoxification enzyme genes such as NAD(P)H, quinone oxidoreductase (NQO1), and heme oxidase-1(HO-1) [ 15 , 16 ]. The protective effect of Nrf2 on the heart has also been confirmed in many animal models, including uncompensated cardiac remodeling and cardiac dysfunction caused by aortic arch constriction (TAC), ventricular remodeling, and cardiac dysfunction caused by myocardial infarction, etc.…”
Section: Discussionmentioning
confidence: 99%
“…AKG via glutamine production can alleviate ROS stress in cells. In the intestinal cells, glutamine can elevate glutathione concentrations [ 68 , 69 ]. Glutathione is one of the most potent ROS scavengers, reducing ROS during self-oxidation [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione is one of the most potent ROS scavengers, reducing ROS during self-oxidation [ 70 ]. Moreover, glutamine can activate the NRF2/ARE signaling pathway and increase NRF2 gene expression [ 69 , 71 ]. SOD and CAT levels increased in murine liver due to the upregulation of NRF2 [ 72 ], conferring better protection against ROS damage.…”
Section: Discussionmentioning
confidence: 99%
“…Sesamin, a naturally occurring lignin compound, is isolated from sesame seeds and has many positive health effects, including anti-inflammatory, anticancer, anti-hypertension, anti-thrombotic, antidiabetic, anti-atherogenic, anti-obesity, and lipolytic effects ( Dalibalta et al, 2020 ). It also can reduce damage to the intestine, kidneys, heart, brain, and liver ( Wang et al, 2021b ). Studies have shown that sesamin inhibits LPS-induced macrophage-derived chemokine expression through ER, PPAR-α, MAPK-p38 pathway, NFκB-p65 pathway, and epigenetic regulation ( Hsieh et al, 2014 ).…”
Section: Antiatherosclerotic Herbal Medicine Potentially Targeting Tr...mentioning
confidence: 99%